A importância das habilidades comportamentais no processo de contratação das empresas: Uma análise a partir da percepção dos alunos do curso de Administração de uma IES pública - Moura, Julyana Queiroz de (Brasil, 2024)
The transformations in the job market have increased the importance of soft skills, which have become indispensable for professionals, complementing technical skills. Despite this growing relevance, higher education institutions are challenged in terms of developing these skills in higher education teaching. In this context, the objective of the research is to analyze the perception of students on the Administration course at a public Higher Education Institution about this reality. Through quantitative research, a questionnaire was applied to outline the demographic profile of the respondents, in addition to investigating their perceptions about the importance of the soft skills required by the global job market and the skills they possess. The results showed that these skills are fundamental for both professional development and organizational success. Therefore, it is concluded that the higher education institution needs to make adjustments to its pedagogical practices to train students aligned with the profile required by the job market.